Social Distancing to Avoid SARS-CoV-2 Infection in Cancer and Noncancer Patients. Issue 8 (7th December 2022) - Kloecker, Goetz; Nolan, Joseph; Korbee, Leslie; Calhoun, Royce; Logan, Barbara; Flora, Dan; Flora, Douglas; Hartman, Philip
Abstract : Background: Social distancing has been recommended by the Centers for Disease Control and Prevention to avoid exposure to SARS-CoV-2 ( Epidemiol Prev 2020;44:353–362). Cancer patients on or after active therapy seem to be more prone to COVID being symptomatic and life-threatening. When evaluating cancer patients' risk of acquiring COVID, it is essential to know the behavior of cancer patients that will affect their risk of exposure. However, it is not known to what degree social distancing is practiced by cancer patients compared with noncancer patients and what factors lead to the decision to distance oneself. Method: After a pilot phase using patients' MyChart messaging, links to the electronic questionnaires were texted to patients using Twillio. Responses were stored on REDCap (Vanderbilt University, Nashville, TN). Six questions about their social distancing behavior and mask wearing were posed and responses were compared between cancer and noncancer patients. Demographics, comorbidities, and a questionnaire about anxiety (Generalized Anxiety Disorder 7-item scale) were recorded. To assess differences between cancer and noncancer groups, Bonferroni-corrected χ 2 tests and proportions confidence intervals were used. Results: The pilot survey was sent in mid-2020 and the full survey followed in January 2021 during a high community COVID incidence. Three hundred eighty-seven cancer patients (32.4% responded) and 503 noncancer patients (22.9% responded) completed the survey. Questions about leaving their houses, driving, shopping, friends, and family indicated that patients with cancer are more cautious ( P < 0.001). Cancer patients were up to 20% more likely to distance themselves. No difference was seen in wearing a mask—both groups wore approximately 90% of the time. Most respondents were female (63% versus 71%). Cancer patients were older (>60 y, 69% versus 45%) and less likely to work (52% versus 31%) or less likely to be White collar workers (21% versus 38%). In both groups, 54% marked "not at all anxious." Conclusions: Cancer patients' responses revealed a distancing behavior that would likely lower the risk exposure to SARS-CoV-2. It is unclear which of the demographic differences would account for this behavior, although remarkably anxiety was not a clear motivating factor. The high acceptance of masks is encouraging. Early publications during the pandemic and patient education suggesting a higher COVID risk for cancer patients may have reduced risk prone behavior. Considering COVID's impact on the vulnerable cancer population and uncertainty in immunosuppressed patients about clearing the virus or adequately responding to a vaccine, further studies about health behavior and health promotion during the pandemic are needed.